Three Essays on Household Finance - Rashed Isam Rashed Ashqar (2022)
This thesis is composed of three research essays aimed at investigating the influence of personality, culture, and religion on household financial dimensions in the European setting. All the empirical studies conducted in this thesis recur to the European Union Statistics on Income and Living Conditions (EU-SILC) dataset from Eurostat. The second chapter examines the impact of personality traits (Neuroticism, Extraversion, and Agreeableness) on some dimensions of household finance in 31 European countries. We employ regression analysis to provide a better understanding of the determinants of the decision to hold secured debts and the likelihood of being in a state of financial distress and financial well-being. Our main findings suggest that the levels of neuroticism and extraversion are negatively associated with the likelihood of holding a mortgage; and that the levels of neuroticism and extraversion (agreeableness) are positively (negatively) associated with the likelihood of being in a state of financial distress. The third chapter explores the influence of Hofstede's national cultures (Power Distance, Masculinity, Individualism, Uncertainty avoidance, Long-term Orientation, and Indulgence) on the likelihood of holding a mortgage and likelihood of being in a state of financial well-being in the same group of 31 European countries. This chapter employs regression analysis using mainly Hofstede's cultural dimensions to conclude that the levels of power distance, masculinity, uncertainty avoidance, and long-term orientation are negatively associated with the likelihood of holding a mortgage. The findings also show the higher the levels of masculinity, uncertainty avoidance, long-term orientation, and indulgence of the national culture in question, the lower the amount of mortgage owned by individuals. Moreover, the levels of individualism and long-term orientation (power distance and uncertainty avoidance) are positively (negatively) associated with the likelihood of being in a state of financial well-being. The fourth chapter investigates the effect of religious backgrounds (Catholic, Orthodox, and Protestant) and religiosity on the likelihood of holding a mortgage and being in a state of financial distress and financial well-being in 32 European countries. We recur to regression analysis of the information on religions to find that belonging to a mainly Catholic or Orthodox (Protestant) country is negatively (positively) associated with the likelihood of holding a mortgage. Moreover, belonging to a Catholic (Protestant) country is negatively (positively) associated with the likelihood of being in a state of financial distress. The results also depict that the levels of religiosity observed in a country are negatively associated with the likelihood of holding a mortgage and the likelihood of being in a state of financial distress. Collectively, our research suggests that variables related to personality, culture, and religion are crucial to understand several financial dimensions in the field of household finance. Moreover, our results offer recommendations to households, policymakers, and academia on the determinants of the likelihood of holding secured debts and a better explanation of the likelihood of being in the states of financial distress and financial well-being.